(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the linguistic and cultural differences in gender characteristics between English and Uzbek languages.By analyzing grammatical structures,lexical choices,patterns, and cultural perspectives,the study aims to indetify how gender is represented and conveyed differentely in both languages.The discussion includes theoriticasl insights from linguists,relevant statistical dasta, and implications for language learners and educators.